College Student Writers' Use and Modification of Planning and Evaluation Strategies After a Semester of Instruction - Philippakos, Zoi A. Traga; MacArthur, Charles A.; Munsell, Sarah (Journal of adolescent & adult literacy, 2018)
The purpose of this study was to investigate how students in a developmental writing course at a community college used and adapted cognitive writing strategies learned in the course. The students participated in a funded research project for the development and evaluation of a writing curriculum based on self‐regulated strategy instruction. The authors investigated students’ application of the planning and revising strategies using think‐aloud protocols. The results showed that students remembered the strategies but did not use them consistently. Also, students tended to use an outline but not always effectively. Finally, reading comprehension seemed to impact their use of revision strategies. Limitations and implications for future research are discussed.